IMPLEMENTATION OF URGENT REASONS FOR MARRIAGE DISPENSATION APPLICATIONS IN THE JUDGES' CONSIDERATIONS AT THE BOJONEGORO RELIGIOUS COURT - Bahij, Nauval -; Prima Anggriawan, Teddy (Jurnal Meta-Yuridis, 2025)
Early marriage is a significant issue in Indonesia, especially for young women, with efforts such as granting marriage dispensations for couples underage by law. This study examines the application of urgent reasons in marriage dispensation requests at the Bojonegoro Religious Court and how judges consider these factors in their decisions. Using empirical legal research, data was collected through interviews with judges and analysis of regulations like Supreme Court Regulation No. 5 of 2019 and Law No. 16 of 2019. Findings reveal that common urgent reasons include premarital pregnancy, relationships resembling marriage, and having children before marriage. However, reasons based on closeness, though frequent, don’t meet legal criteria but are considered based on the couple's physical and mental readiness. Key obstacles in applying urgent reasons involve legal, law enforcement, societal, and cultural factors. The study recommends enhancing oversight and educating the public on the consequences of early marriage.